Modelo Prolab, Coworkkids, una propuesta de networking con equilibrio entre familia y trabajo para las personas de Arequipa, 2024 - Calla Huayapa, Maxgabriel Alexis (2024)
The coworking business model has experienced continuous and significant growth, adapting to emerging trends in the labor market. The demand for new non-traditional work modalities has increased, driven by the need to reduce costs and the adoption of hybrid work models; in addition, these spaces allow mentoring, networking and the creation of particular communities, marking the direction of this business. It also helps to balance family life with children, allowing for scenarios where skills can also be developed with them without being far away, and with the confidence of the children’s well-being, which allows the bond not to be lost, avoiding frustrations in the future. The business model has been validated through experiments that allow the hypotheses raised to be addressed effectively, also considering Monte Carlo simulations with high efficiency indicators, this added to a financial and social profitability that contribute to the effectiveness of the business model. Coworkkids not only generates an economic NPV of 4,469,632.16 soles, and an IRR of 67.86% in a five-year projected flow, but also a social NPV of 6,332,774.00 soles at a discount rate of 8%, confirming that it is an efficient, profitable and sustainable project and facilitates the fulfillment of each of the objectives based on sustainable development.